STRATEGI GURU IPS DALAM PEMBENTUKAN SIKAP SOSIAL SISWA DI SMP NEGERI 2 SAMBAS - Bayu Bayu (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2025)
This study aims to describe the strategies employed by Social Studies (IPS) teachers in shaping students' social attitudes at SMP Negeri 2 Sambas, as well as the efforts made to overcome the challenges encountered in the process. This research adopts a descriptive qualitative approach. Data collection techniques include interviews, observation, and documentation. The findings indicate that the strategies used by Social Studies teachers to develop students’ social attitudes include humanistic, spiritual (religious), and behavioral approaches. Additionally, teachers implement strategies such as providing examples, giving advice, offering rewards, and applying direct individual approaches to students. Another strategy involves forming student work groups to foster a sense of togetherness and cooperation. The teachers' efforts to address challenges in shaping social attitudes include using personal, religious, and behavioral approaches, giving guidance, and applying educational sanctions. These findings highlight the crucial role of teachers in shaping students’ social character through adaptive strategies rooted in humanitarian and religious values